2014
DOI: 10.1007/s00248-014-0478-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Associates of the Vine Mealybug Planococcus ficus (Hemiptera: Pseudococcidae) under Different Rearing Conditions

Abstract: Sap-feeding insects harbor diverse microbial endosymbionts that play important roles in host ecology and evolution, including contributing to host pest status. The vine mealybug, Planococcus ficus, is a serious pest of grapevines, vectoring a number of pathogenic grape viruses. Previous studies have shown that virus transmission is abolished when mealybugs are raised in the laboratory on potato. To examine the possible role of microbial symbionts in virus transmission, the archaeal, bacterial, and fungal micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 69 publications
(70 reference statements)
1
12
0
Order By: Relevance
“…While the reason for this difference is not clear and should be further studied, it appears that lineages of these hypocrealean fungi have undergone a shift from insect pathogens to mutualists (or nonpathogens, or at least sublethal pathogens). Other fungi that were found in our study— Cladosporium , Alternaria and Wallemia —were also reported from a mealybug (Sternorrhyncha: Pseudococcidae, a sister taxon to Coccidae) (Iasur‐Kruh et al., ). In the light of our results, we postulate that these fungi are facultatively or opportunistically associated with soft scales.…”
Section: Discussionsupporting
confidence: 76%
“…While the reason for this difference is not clear and should be further studied, it appears that lineages of these hypocrealean fungi have undergone a shift from insect pathogens to mutualists (or nonpathogens, or at least sublethal pathogens). Other fungi that were found in our study— Cladosporium , Alternaria and Wallemia —were also reported from a mealybug (Sternorrhyncha: Pseudococcidae, a sister taxon to Coccidae) (Iasur‐Kruh et al., ). In the light of our results, we postulate that these fungi are facultatively or opportunistically associated with soft scales.…”
Section: Discussionsupporting
confidence: 76%
“…Ascomycetous yeast of the genus Candida and basidiomycetous yeast of the genus Asterotremella were shown to produce xylanase and carboxymethyl cellulose in insects and their natural habit 47 . Wallemia and Cladosporium are very common environmental fungal genera that associate with many plants as commensals and pathogens 48 . These microbial groups are widespread, ecologically diverse, and functionally redundant in organic matter decomposition and lignocellulose digestion and may be transiently acquired by insects from feeding materials and the environment 10 .…”
Section: Discussionmentioning
confidence: 99%
“…For the fungal community, Wallemia was more abundant in nymph and adult stages than in the egg stage; a similar trend was also observed in genera Papiliotrema . Wallemia could be transiently acquired by insects from feeding behavior and the environmental habitat, because this fungal group commonly acted as commensals and opportunistic pathogens for many plants (Iasur‐Kruh et al ., ). Exploring the accurate transmission patterns of these microbes associated with BPH would be the next step in further work.…”
Section: Discussionmentioning
confidence: 97%